Prevalence and determinants of perceived stress among undergraduate students in a Malaysian University - Fam, Jia Yuin *; Teo, Loo Yee (Faculty of Medicine, University of Malaya, 2018)
Introduction: Studying in a university can be stressful for any undergraduate student, and the excessive stress is associated with physical and mental health problems. The purpose of the study was to examine the prevalence and determinants of perceived stress among undergraduate students in a Malaysian university. Methods: 456 undergraduate students participated in this study. The Perceived Stress Scale and the Student Stress Survey ( SSS) were implemented as indicators; PSS as a global measure of perceived stress, and the SSS for the identification of the sources of stress. Results: The prevalence rate of perceived stress among the undergraduate students was 37.7%. The overall PSS mean score was 27.5 ( SD 4.763), with a cut-off value of perceived stress at 28. Multivariate logistic regression model identified that the female student (OR 1.995, 95% CI 1.313-3.031) and the first year student (OR = 2.383, 95% CI 1.047-5.422) perceived more stress than the others. Conclusion: The present study demonstrated a high prevalence rate of perceived stress among undergraduate students in general, and the female and the first year undergraduate students in particular. There is a need for further studies on the borderline stress of the undergraduate students and the sources of stress.